Sustainability Analysis of Existing Agriculture on High Risk Erosion Area (Case Studies in Lembang, West Bandung District and in Dongko, Trenggalek District) - RACHMI WIDIRIANI; SUPIANDI SABIHAM; S. HADI SUTJAHJO; IRSAL LAS (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
There are three main constraints for the upland agriculture development, namely (1) steep slopes that limit the suitable farm land, (2) soil erosion rate tends to be higher than the rate of soil losses and (3) high average annual rainfall. This research focused on sustainability analysis at high risk erosion area in Lembang sub district and Dongko sub district. The aim of this research was to analyze index and sustainability status of the border area, existing farming on high risk erosion. Multi Dimension Scalling-Rapid appraisal for farming (MDS-Rapfarm) technique was used for evaluating the sustainability of existing farming based on five sustainable indicators i.e. ecology, economy, social, local organization, and technology. Soil analysis and USLE method were used to predict erosion rate and soil fertility. The result of the MDS analysis showed that sustainable multi-dimension index (ecology, economy, social, local organization, technology) of Lembang sub district was 35,47; 38,15; 56,42; 34,49; 17,30;and Dongko sub district was 24,16; 47,13; 63,78; 64,78; 41,55 (on scale 0-100). The average of soil loss in Lembang was predicted 147,29 t ha-1 year-1 and in Dongko was 245,95 t ha-1 year-1 on average. Attributes being sensitive in increasing index and sustainability status were: source of organic matter, perennial proportion, farmer oriented on agriculture extension, social conflict intensity, annual rainfall, land solum, land conversion, and number of agriculture household.